High-entropy alloy and method for manufacturing a high-entropy alloy
Patent Information
- Application Number
- JP2024159158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-09-13
AI Technical Summary
【0027】 本発明のハイエントロピー合金は、高硬度であって低放射化合金であるハイエントロピー合金を提供できる。 本発明のハイエントロピー合金の製造方法によれば、高硬度であって低放射化合金であるハイエントロピー合金を容易に製造できる。
Smart Images

Figure 0007933327000010 
Figure 0007933327000011 
Figure 0007933327000012
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a high-entropy alloy and a method for producing the high-entropy alloy. BACKGROUND ART
[0002] In general, a high-entropy alloy is composed of multi-component elements of 5 or more components. Further, the high-entropy alloy is an alloy whose composition is an equiatomic composition or close to an equiatomic composition, and which has a single solid solution or a plurality of or more crystal structures.
[0003] Properties unique to high-entropy alloys include stabilization of disordered solid solution phases (High entropy effect), severely distorted crystal lattices (Severe Lattice distortion effect), slow atomic diffusion (Sluggish diffusion effect), and cocktail effect (Cocktail effect).
[0004] The High entropy effect increases the effect of the entropy term on the phase stability of the alloy. The Severe Lattice distortion effect is an effect that the yield stress increases significantly because, when compared with conventional alloys, a simple crystal structure is formed from various component elements with different atomic radii in a high-entropy alloy, resulting in potential distortion in the lattice.
[0005] The Sluggish diffusion effect is that in high-entropy alloys, the diffusion coefficient decreases due to various interatomic bonds in the lattice, lattice distortion, and the like, so that the solid solution can exist stably and also has creep resistance properties.
[0006] The Cocktail effect is a non-linear effect that cannot be explained by a simple summation (additivity rule) of the physical properties of the constituent metal elements. Known examples of high-entropy alloys include Patent Document 1, Patent Document 2, Patent Document 3, and Patent Document 4.
[0007] Patent Document 1 proposes a high-entropy alloy containing elements Co, Cr, Fe, Ni, Mo, Ti, Ta, and Nb in a predetermined range of at% or more and at% or less, with the remainder consisting of unavoidable impurities.
[0008] Patent Document 2 proposes an alloy substrate comprising an alloy base material containing 5 at% to 35 at% of each of five elements such as Co, and Mo in a range of more than 0 at% and 8 at% or less, with the remainder being unavoidable impurities, and an alloy member having a surface treatment phase on the surface of the substrate consisting of a nitride containing Ti, etc.
[0009] Patent Document 3 proposes an alloy member that contains Co, Cr, Fe, Ni, and Ti in a predetermined range of at% or more and at% or less, with the remainder being unavoidable impurities, and having a Vickers hardness of 550 HV or more.
[0010] Patent Document 4 proposes a high-entropy alloy containing Ti, Zr, Nb, and Ta, as well as at least one element from the Mo, Hf, W, V, and Cr group. Non-patent document 1 discloses the Vickers hardness of high-entropy alloys when various additives are added. [Prior art documents] [Patent Documents]
[0011] [Patent Document 1] Patent No. 7311053 [Patent Document 2] Patent No. 7248196 [Patent Document 3] Patent No. 7173397 [Patent Document 4] Patent No. 6979184 [Non-patent literature]
[0012] [Non-Patent Document 1] Wei Zhang, et al., "Additive manufactured high entropy alloys: A review of the microstructure and properties," p. 19, Fig. 16, [online], June 2022, Materials & Design, Vol. 220, 2022, 110875 (pp. 1-40)), [Retrieved June 20, 2024].<https: / / www.sciencedirect.com / science / article / pii / S026412752200497X?via%3Dihub> [Overview of the project] [Problems that the invention aims to solve]
[0013] Incidentally, the Vickers hardness (HV) of the high-entropy alloy disclosed in Patent Document 1 is in the range of 455 to 497. In the example of an alloy member described in Patent Document 2, it is disclosed that the hardness (Rockwell hardness (HRC)) is in the range of 40.9 to 59.9. This hardness corresponds to a Vickers hardness (HV) range of 392 to 697.
[0014] The Vickers hardness (HV) of the alloy member disclosed in Patent Document 3 is in the range of 550 to 680. Patent Document 4 discloses that the high-entropy alloy has high strength and can be applied as a biocompatible material.
[0015] Among the high-entropy alloys disclosed in Non-Patent Document 1, the one with the highest Vickers hardness (1400) is AlCoCrCuFeNi+WC. In this high-entropy alloy, WC is added to AlCoCrCuFeNi by L-PBF (Laser Powder Bed Fusion).
[0016] The aforementioned Patent Documents 1 to 3 disclose examples of high-entropy alloys with high hardness. However, depending on the application of the high-entropy alloy, the strength of the high-entropy alloys listed above may be insufficient, and further development of high-entropy alloys with higher hardness is desired.
[0017] For example, in applications such as materials for nuclear fusion reactors that are used while being exposed to intense radiation, alloys exceeding the strength of the aforementioned high-entropy alloys are desired, and the application of alloys composed of low-activation elements is required.
[0018] In Patent Document 4, development is being advanced mainly from the perspectives of biocompatible materials and hardness improvement. As a result, since the alloy is designed with constituent elements that do not take low-activation properties into consideration, activation occurs in specific applications used in radiation environments, and it is anticipated that problems such as management costs and disposal of the relevant material will arise in the future.
[0019] In Non-Patent Document 1, L-PBF (laser powder bed fusion) is used to add WC to a high-entropy alloy. For this reason, after the high-entropy alloy is produced, an additional treatment step for adding the additive is required, which is labor-intensive and costly.
[0020] An object of the present invention is to solve the above problems and provide a high-entropy alloy that is a high-hardness, low-activation alloy. Another object of the present invention is to provide a method for producing a high-entropy alloy that can easily produce a high-entropy alloy which is a high-hardness, low-activation alloy. [Means for Solving the Problems]
[0021] The high-entropy alloy of the present invention contains each element of W (tungsten), Si (silicon), Fe (iron), Cr (chromium), and V (vanadium) at 5 at% or more and 35 at% or less, with the balance being unavoidable impurities.
[0022] In the present specification, the crystal structure includes solid solutions and intermetallic compounds. Furthermore, the high-entropy alloy has a mixed entropy ΔS mix However, it is preferable that it be 1.5R or higher.
[0023] Furthermore, the high-entropy alloy is It is a multi-phase type, Crystal structure with at least three phases or more Phases with different elemental concentrations It's good to have. Furthermore, the high-entropy alloy has a Vickers hardness in its crystal structure. 1100~1800 (HV) It is preferable to include the following parts.
[0024] Furthermore, the high-entropy alloy has a Vickers hardness in its crystal structure. 1300~1800 (HV) It is good to include the part. 。
[0025] Book The invention provides a method for producing a high-entropy alloy, comprising a melting step of dissolving raw materials containing the aforementioned elements, a cooling step of cooling the molten metal produced in the melting step, and a homogenization step of heating and pressurizing the high-entropy alloy cooled in the cooling step to homogenize it.
[0026] Furthermore, the homogenization step is preferably a process of heating and pressurizing by hot isostatic processing or hot pressing. Furthermore, the dissolution process may include a first pre-dissolution process for dissolving Si (silicon) and W (tungsten), a second pre-dissolution process for dissolving Cr (chromium) and W (tungsten), a third pre-dissolution process for dissolving Fe (iron) and W (tungsten), and a later dissolution process for mixing and dissolving the products obtained in the first, second, and third pre-dissolution processes, respectively, and V (vanadium). [Effects of the Invention]
[0027] The present invention provides a high-entropy alloy that is a high-hardness, low-activation alloy. According to the method for producing high-entropy alloys of the present invention, high-entropy alloys that are hard and low-activation alloys can be easily manufactured. [Brief explanation of the drawing]
[0028] [Figure 1] (a) is a process diagram of a manufacturing method according to one embodiment of the present invention, and (b) is a process diagram showing a subdivided dissolution process. [Figure 2] (a) is a photograph of the cross-section obtained by cutting a high-entropy alloy by wire EDM before the homogenization process, and (b) is a photograph of the cross-section obtained by cutting a high-entropy alloy by electrical discharge machining after the homogenization process. [Figure 3] (a) is a photograph showing a portion of the high-entropy alloy after the homogenization process has been cut by wire cutting, (b) is a magnified photograph of the cut surface of a portion of the alloy, and (c) is a photograph of the entire cut surface including the magnified area of (b). [Figure 4] This graph shows the Vickers hardness at various measurement points in the low-density and high-density regions of the manufactured alloy. [Figure 5] (a) is a photograph of the entire cross-section, the same as in Figure 3(c), (b) is a cross-sectional photograph showing a magnified portion of the surface area of (a), (c) is a cross-sectional photograph showing a magnified portion of the surface area of (b), and (d) is a cross-sectional photograph showing a magnified portion of the surface area of (c). [Figure 6] (a) is a SEM image of a high-entropy alloy, (b) is an elemental concentration map of Fe obtained by energy-dispersive X-ray spectroscopy (EDS) of the same region (EDS image), (c) is an elemental concentration map of W of the same region (EDS image), (d) is an elemental concentration map of Cr of the same region (EDS image), (e) is an elemental concentration map of Si of the same region (EDS image), and (f) is an elemental concentration map of V of the same region (EDS image). [Modes for carrying out the invention]
[0029] <High-entropy alloys> The high-entropy alloy in this embodiment is defined by (A) the number and composition of constituent elements, and (B) the entropy of the mixture.
[0030] According to the definition based on the number and composition of constituent elements, a high-entropy alloy is one in which the number of major constituent elements is 5 or more, the proportion of major constituent elements is between 5 at% and 35 at%, and the proportion of minor elements is between 0 at% and 5 at%.
[0031] The main constituent elements of the high-entropy alloy in this embodiment are W (tungsten), Fe (iron), Si (silicon), V (vanadium), and Cr (chromium). The composition ratio of the main constituent elements is 5 at% to 35 at%, while the proportion of minor elements, which are unavoidable impurities, is between 0 at% and 5 at%.
[0032] The proportion of the main constituent elements is more preferably 8 at% or more, and particularly preferably 12 at% or more. Furthermore, the proportion of the main constituent elements is more preferably 30 at% or less, and particularly preferably 28 at% or less.
[0033] Furthermore, the definition of high-entropy alloys based on (B) the entropy of the mixture is as follows: High-entropy alloys are stabilized because the entropy of mixture term in Gibbs' free energy equation (see equation (1)) increases negatively.
[0034]
number
[0035] The entropy term of the mixture of random ideal solutions is given by equation (2).
[0036]
number
[0037]
number
[0038] As is clear from equation (3) above, alloys with an equiatomic composition have the highest entropy, and entropy increases with increasing number of components. Alloys with high entropy exhibit a stable mixed state. These high-entropy alloys yield complex and fine-grained metallic structures. This structure exhibits excellent diffusion and significant lattice distortion due to differences in atomic radii. The increased deformation resistance resulting from this large lattice distortion leads to high hardness in these alloys.
[0039] From the above perspective, in a definition based on mixing entropy, a mixing entropy ΔSmix of 1.5R or greater is preferable. (Inevitable impurities) While it is difficult to completely remove unavoidable impurities during the manufacturing process, it is desirable to reduce them as much as possible.
[0040] Therefore, the total content of unavoidable impurities is preferably 1% by mass or less. In other words, the total content of elements intentionally included (W (tungsten), Fe (iron), Si (silicon), V (vanadium), and Cr (chromium)) is preferably 99% by mass or more of the total mass of the alloy.
[0041] W (tungsten), Fe (iron), Si (silicon), V (vanadium), and Cr (chromium) are low-entropy elements. Therefore, the high-entropy alloy of this embodiment, since it is made from these elements, is an alloy with low-entropy properties.
[0042] H, He, Li, Be, B, C, N, O, F, Ne, Na, Mg, Mn, Ga, Ge, As, Se, Sb, I, Ti, and Pr are also low-activation elements. When high-entropy alloys containing these elements as unavoidable impurities are used as materials for nuclear fusion reactors, the low-activation properties do not pose a problem.
[0043] P, S, Cl, Ca, Sc, Ti, Zn, Br, Rb, Sr, Y, Zr, Ru, In, Sn, Te, Ta, Au, La, and Ce are alloying elements and do not adversely affect low-activation. Therefore, they do not adversely affect the low-activation properties of high-entropy alloys that have these elements as unavoidable impurities.
[0044] Furthermore, the inventor manufactured a high-entropy alloy based on the above-mentioned elemental raw materials for application in equipment requiring high strength, heat resistance, and irradiation resistance, such as materials for nuclear fusion reactors. Through this manufacturing process, the inventor was able to obtain a high-entropy alloy with a hardness that could not be achieved with conventional high-entropy alloys.
[0045] This high-entropy alloy is a multi-phase alloy system that sets it apart from common compound-based cemented carbide materials (e.g., WC, sapphire, etc.). <Method for manufacturing high-entropy alloys> The method for producing the high-entropy alloy of this embodiment will be described below.
[0046] Figure 1(a) is a process diagram of the method for producing a high-entropy alloy according to the present invention. As shown in the figure, the method for producing a high-entropy alloy includes a melting step S10, a cooling step S20, and a homogenization step S30.
[0047] (Dissolution step S10) The dissolution process S10 includes a first early dissolution process S11, a second early dissolution process S12, a third early dissolution process S13, and a later dissolution process S14, as shown in Figure 1(b).
[0048] The reason why the dissolution process is carried out in multiple stages is that, among these five elements, W (tungsten), which has the highest melting point, can be dissolved efficiently. When the dissolution process is carried out in multiple stages, in the first pre-dissolution process S11, the second pre-dissolution process S12, and the third pre-dissolution process S13, W (tungsten) is commonly dissolved with the raw materials of the other elements, as will be described later.
[0049] The total amount of tungsten (W) required is weighed to match the composition ratio [at%] of the final high-entropy alloy produced. This total amount of tungsten is then divided into three parts, each used in a separate melting process. While this division into three parts is possible, it is not limited to three equal parts.
[0050] (First early dissolution step S11) The first pre-dissolution step S11 is a dissolution step of W (tungsten) and Si (silicon). In the first pre-dissolution step S11, the raw materials for W (tungsten) and Si (silicon) are dissolved, for example, by an arc dissolution method under an inert gas atmosphere. The form of these raw materials may be powder, granules, lumps, etc.
[0051] Furthermore, the amount of Si (silicon) is weighed so that it matches the composition ratio [at%] in the final high-entropy alloy produced. The heating temperature in the first pre-dissolution step S11 may be a temperature exceeding the melting point determined according to the composition ratio of the two elements. This melting point can be determined by referring to the known two-component equilibrium phase diagrams of both elements.
[0052] Specifically, the melting point of tungsten (W) is 3422°C. The melting point of Si (silicon) is 1414°C. Therefore, the heating temperature determined in the first pre-melting step S11 according to the composition ratio of the two elements is in the range of 1414°C to 3422°C, and should be at least above 1414°C.
[0053] The melting method is not limited to arc melting; other melting methods may also be used. After the melting of W (tungsten) and Si (silicon) is complete, it is preferable to cool the mixture until it becomes a solid, but it may also be left in a molten state. Hereinafter, the material that has been melted in the first pre-melting step S11, the second pre-melting step S12, and the third pre-melting step S13 will simply be referred to as the manufactured product.
[0054] (Second early dissolution step S12) The second pre-dissolution process S12 is the dissolution process of W (tungsten) and Cr (chromium). In the second pre-dissolution step S12, the raw materials for W (tungsten) and Cr (chromium) are dissolved, for example, by arc dissolution under an inert gas atmosphere. These raw materials may be in powder, granular, or lump form.
[0055] Furthermore, chromium (Cr) is weighed to match the final composition ratio [at%] in the high-entropy alloy produced. The heating temperature in the second pre-dissolution step S12 may be a temperature exceeding the melting point determined according to the composition ratio of the two elements. This melting point can be determined by referring to the known two-component equilibrium phase diagrams of both elements.
[0056] Specifically, the melting point of chromium (Cr) is 1907°C. Therefore, the melting point determined according to the composition ratio of the two elements in the second pre-melting step S12 will be in the range of 1907 to 3422°C, and will be at least above 1907°C.
[0057] The melting method is not limited to arc melting; other melting methods may also be used. After the dissolution of W (tungsten) and Cr (chromium) is complete, it is preferable to cool the mixture until it becomes a solid, but it may also be left in a molten state.
[0058] (Third early dissolution step S13) The third, early dissolution process S13 is the dissolution process of W (tungsten) and Fe (iron). In the third pre-melting step S13, the raw materials W (tungsten) and Fe (iron) are melted, for example, by arc melting under an inert gas atmosphere. These raw materials may be in powder, granular, or lump form.
[0059] Furthermore, the amount of Fe (iron) is weighed to match the composition ratio [at%] in the final high-entropy alloy produced. The heating temperature in the third pre-dissolution step S13 may be a temperature exceeding the melting point determined according to the composition ratio of the two elements. This melting point can be determined by referring to the known two-component equilibrium phase diagrams of both elements.
[0060] Specifically, the melting point of Fe (iron) is 1538°C. Therefore, the melting point determined according to the composition ratio of the two elements in the third pre-melting step S13 will be in the range of 1538 to 3422°C, and will be at least above 1538°C.
[0061] The melting method is not limited to arc melting; other melting methods may also be used. After the melting of W (tungsten) and Fe (iron) is complete, it is preferable to cool the mixture until it becomes a solid, but it is also acceptable to leave it in a molten state.
[0062] (Late dissolution step S14) The late dissolution step S14 is a step in which the products obtained in the first early dissolution step S11, the second early dissolution step S12, and the third early dissolution step S13 are mixed with vanadium(V) and vanadium(V) is dissolved. In the late dissolution step S14, vanadium(V) is dissolved, for example, by an arc dissolution method under an inert gas atmosphere. The form of the vanadium(V) raw material may be powder, granules, lumps, etc.
[0063] Vanadium (V) is weighed to match the final composition ratio [at%] in the high-entropy alloy produced. The melting point of vanadium(V) is 1910°C. In this dissolution process, the dissolved raw materials will be multi-component. Therefore, heating may be done at a temperature below 1910°C. However, the heating temperature may also be above 1910°C.
[0064] The melting method is not limited to arc melting; other melting methods may also be used. (Cooling process S20) The cooling process S20 is a process of cooling the product after it has been dissolved in the dissolution process S10. It is preferable to cool the product by natural cooling until it becomes solid.
[0065] (Homogenization step S30) For the homogenization step S30, a hot isostatic pressing (HIP) method is preferred, for example. The hot isotropic pressurization method is carried out at a temperature of 1000°C or higher, preferably 1050°C or higher, and more preferably 1150°C or higher. The processing time is preferably between 1 hour and 10 hours, but is not limited to that.
[0066] If the temperature is too low, the material will not reach a usable density for processing, and if it is too high, rapid grain growth will cause large voids to form locally, which is undesirable. If the pressure applied by pressurization is too low, the material will not reach a usable density for processing. If the temperature is too high, the hot isostatic processing equipment will wear out quickly.
[0067] The gas pressure used in the hot isotropic pressurization method is generally about 100 megapascals (MPa) or more, preferably about 150 MPa or more, and more preferably about 200 MPa or more. Preferred gases used in this hot isotropic pressurization method are not particularly limited, but include argon, nitrogen, helium, xenon, and mixed gases containing one of these.
[0068] In the homogenization process S30, in addition to the hot isostatic pressing method, the process may also be carried out by the hot uniaxial pressing method (hot press method). Furthermore, the hot uniaxial pressing method (hot press method) may be performed before or after the hot isostatic pressing (HIP) process.
[0069] The homogenization process S30 homogenizes the segregation of the alloy's component concentrations and removes casting defects. <Examples> The high-entropy alloys of the examples and the methods for producing these high-entropy alloys will be described.
[0070] In the examples, the raw materials for each element were weighed so that the composition ratio ([at%]) of each element in the final high-entropy alloy produced was as shown in Table 1 below. Table 1 below shows the mass and composition ratio ([mass%] and [at%]) of each element.
[0071] Mixed entropy ΔS of the high-entropy alloy in this embodiment mix This is 1.5666R (>1.5R).
[0072] [Table 1] The method for producing the high-entropy alloy in this embodiment is as follows.
[0073] (First early dissolution step S11) In the first pre-melting step S11, solid tungsten (W) and solid silicon (Si) raw materials are melted by arc melting under an inert gas atmosphere. The mixing ratio of tungsten and silicon should be determined by referring to the phase diagram of the binary alloy and setting the mixing ratio to a temperature at which melting is possible by arc melting.
[0074] Specifically, the amount of tungsten (W) shown in the table was divided into three equal parts, and the silicon (Si) raw material was prepared so that it would melt at the melting point (2010°C) of a Si-40at%W composition, referencing a two-component equilibrium phase diagram. After melting, the product was cooled until it became solid.
[0075] (Second early dissolution step S12) In the second pre-melting step S12, solid tungsten (W) and solid chromium (Cr) raw materials are melted by arc melting under an inert gas atmosphere. The mixing ratio of tungsten (W) and chromium (Cr) should be determined by referring to the phase diagram of the binary alloy and setting the mixing ratio to a temperature at which melting is possible by arc melting.
[0076] Specifically, the amount of tungsten (W) shown in the table was divided into three equal parts, and the raw material for chromium (Cr) was prepared so that it would dissolve at the melting point (2000°C) of a Cr-18at%W composition, referencing a two-component equilibrium phase diagram. After dissolution, the product was cooled until it became solid.
[0077] (Third early dissolution step S13) In the third, initial melting process S13, solid tungsten (W) and solid iron (Fe) raw materials are melted by arc melting under an inert gas atmosphere. The mixing ratio of tungsten (W) and iron (Fe) should be determined by referring to the phase diagram of the binary alloy and setting the mixing ratio to a temperature at which melting is possible by arc melting.
[0078] Specifically, the amount of tungsten (W) shown in the table was divided into three equal parts, and the iron (Fe) raw material was prepared so that it would melt at the melting point (1800°C) of a composition of Fe-25at%W, referencing a two-component equilibrium phase diagram. After melting, the product was cooled until it became solid.
[0079] (Late dissolution step S14) In the later dissolution step S14, the products obtained in the first early dissolution step S11, the second early dissolution step S12, and the third early dissolution step S13, along with solid vanadium(V), were mixed, and the vanadium(V) was dissolved by arc dissolution under an inert gas atmosphere.
[0080] Specifically, the amount of vanadium (V) shown in the table and the respective products manufactured in the first to third pre-processing stages were mixed, and the entire mixture was heated and melted at a temperature of 1910°C or lower using the arc melting method.
[0081] As mentioned above, the mixing ratio of vanadium (V) and the aforementioned product should be determined appropriately by referring to the phase diagram, so as to reach a temperature at which it can be dissolved. Therefore, the elemental proportions of the final alloy are preferably in the range of 45% to 76% by mass for W, 3% to 9% by mass for Si, 10% to 21% by mass for Fe, 3% to 20% by mass for Cr, and 4% to 19% by mass for V. In addition to the elemental proportions mentioned above, the final alloy will also contain a proportion of unavoidable impurities.
[0082] (example) Using the example of a total mass of 83.47g for each element in Table 1, the validity of the above ranges for each element can be explained in Tables 2 to 6.
[0083] [Table 2]
[0084] [Table 3]
[0085] [Table 4]
[0086] [Table 5]
[0087] [Table 6] Tables 2 to 6 show examples of the minimum and maximum mass percentage ranges for each element mentioned above.
[0088] The minimum mass percentage of W (45 mass%) is shown in Tables 2, 4, 5, and 6, while the maximum mass percentage (76 mass%) is shown in Table 3. Examples of these mass percentages of W fall within the range of 5 at% to 35 at%.
[0089] The minimum mass percentage of Si (3 mass%) is shown in Tables 2 to 5, and the maximum mass percentage (9 mass%) is shown in Table 6. Examples of Si mass percentages in these tables fall within the range of 5 at% to 35 at%.
[0090] The minimum mass percentage of Fe (10 mass%) is shown in Tables 2 and 3, while the maximum mass percentage (21 mass%) is shown in Tables 4 and 6. Examples of Fe mass percentages in these tables fall within the range of 5 at% to 35 at%.
[0091] The minimum mass percentage of Cr (3 mass%) is shown in Tables 3, 4, and 6, while the maximum mass percentage (20 mass%) is shown in Table 5. Examples of Cr mass percentages in these tables fall within the range of 5 at% to 35 at%.
[0092] The minimum mass percentage of V (4 mass%) is shown in Tables 3 and 5, while the maximum mass percentage (19 mass%) is shown in Table 2. Examples of mass percentages of V in these tables fall within the range of 5 at% to 35 at%. (Cooling process S20) In the cooling process S20, the product that had been dissolved in the dissolution process S10 was allowed to cool naturally until it became a solid.
[0093] Figure 2(a) is an electron microscope image of a cross-section of a part of the manufactured product after cooling, which was cut off by electrical discharge machining. As shown in Figure 2(a), casting defects can be seen on the cut surface. (Homogenization step S30) The products, cooled in S20, were processed by hot isostatic pressing (HIP) at 1300°C for 5 hours at 200 megapascals (MPa) in an argon atmosphere.
[0094] Figure 2(b) is an electron microscope image of a cross-section of a part of the manufactured product after the homogenization process S30, which was cut off by electrical discharge machining. As shown in Figure 2(b), the casting defects have been eliminated from the cut surface.
[0095] <Hardness measurement> The hardness of the cross-section of the high-entropy alloy after the homogenization process S30 was measured. Specifically, hardness measurements (load: 0.1N, indentation time: within 60 seconds) were performed on a portion of the cut surface (see Figure 3(c)) obtained by electrical discharge machining of a high-entropy alloy (see Figures 3(a) and 3(b)). A micro-Vickers hardness tester (Mitsutoyo: Model HM-200) was used for the measurements.
[0096] Figure 3(b) is a magnified photograph of a portion of the cross-sectional photograph of the manufactured product shown in Figure 3(c). As shown in Figure 3(b), hardness measurements were performed on the areas overlapped by dotted lines with arrows extending vertically. Hereafter, the dotted lines with arrows will be referred to as measurement lines L. In Figure 3(b), a predetermined point on the measurement line L is designated as the reference point, with the direction extending downwards being the + side and the opposite side being the - side. The direction extending downwards (+ side) is the surface side of the high-entropy alloy. The direction extending upwards (- side) is the opposite surface side of the high-entropy alloy. In Figure 3(b), the numerical values from -1200 to 2300 represent the distance (μm) from the reference point to the measurement point.
[0097] (low density area) Figure 4 shows the Vickers hardness results for the area overlapped by the measurement line L shown in Figure 3(b). The horizontal axis represents the distance from the reference point to the measurement point. The vertical axis represents the Vickers hardness at each of the 56 measurement points.
[0098] As shown in Figure 4, a region (measurement points P1 to P11) was measured on the opposite surface side where the Vickers hardness remained in the range of approximately 1100 to 1700 (HV). Since the hardness in this region is lower than that of the surface side, this was designated as a low-density region.
[0099] (high density area) As shown in Figure 4, a Vickers hardness of approximately 1300 to 1800 (HV) was measured in the region (measurement points P12 to P20 and P22 to P55).
[0100] No voids were observed in the measurement points P12-P20 and P22-P55, suggesting that homogenization was successful, resulting in a Vickers hardness in the range of approximately 1300-1800 (HV).
[0101] Therefore, this region was designated as a high-density region because its hardness is higher than that of the low-density region. Furthermore, the Vickers hardness at measurement point P21 was approximately 1000 (HV) due to the presence of voids. Therefore, it is believed that homogenization was not performed properly at measurement point P21, and thus measurement point P21 will be excluded from the high-density region.
[0102] (Surface area) Figure 5(a) is a photograph of the entire cross-section, the same as in Figure 3(c). Figure 5(b) is a magnified cross-sectional photograph of the surface area of the cross-section in Figure 5(a). Figure 5(c) is a further magnified cross-sectional photograph of a portion of the surface area in Figure 5(b). Figure 5(d) is a magnified cross-sectional photograph of a portion of the surface area including the measurement point j in Figure 5(c).
[0103] Vickers hardness was measured at 23 locations on the surface, from measurement point a to measurement point w, as shown in Figures 5(b) and 5(c). Measurement points a to w are located closer to the surface than measurement point P55 on the aforementioned measurement line L, and are scattered in the left-right direction in the same figure. Measurement point p is on the extension of the aforementioned measurement line L.
[0104] In Figures 5(b) and 5(c), the numbers preceding measurement points a to w represent the Vickers hardness at that measurement point. As shown in Figures 5(b) and 5(c), Vickers hardness values of 2070 to 3639 (HV) were measured at measurement points a to w. A Vickers hardness of 2070 (HV) corresponds to the value at measurement point f. A Vickers hardness of 3639 (HV) corresponds to the value at measurement point j.
[0105] As shown in Figure 5(d), no cracks (gaps) were observed at measurement point j, where the highest Vickers hardness was measured. (Elemental concentration map (EDS image)) The cross-section of the high-density region of the high-entropy alloy in this embodiment was subjected to energy-dispersive X-ray spectroscopy (EDS). The resulting elemental concentration maps in the cross-section are shown in Figures 6(b) to 6(f).
[0106] Figure 6(a) is an SEM image of the composition plane of the high-entropy alloy in this embodiment. Figure 6(b) is an elemental concentration map (EDS image) of Fe (iron) obtained by energy-dispersive X-ray analysis (EDS) of the same area. Figure 6(c) is an elemental concentration map (EDS image) of W (tungsten) of the same area. Figure 6(d) is an elemental concentration map (EDS image) of Cr (chromium) of the same area. Figure 6(e) is an elemental concentration map (EDS image) of Si (silicon) of the same area. Figure 6(f) is an elemental concentration map (EDS image) of V (vanadium) of the same area.
[0107] In the chromium (Cr) elemental concentration map in Figure 6(d), three regions can be observed: a region of high atomic concentration, a region of intermediate atomic concentration, and a region of low atomic concentration. This indicates that the high-entropy alloy of this embodiment has three phases, each with different crystalline structures at different elemental concentrations among the mixed elements.
[0108] Therefore, because it has three phases in the high-density region, it can be said that there is a clear difference in crystal structure compared to conventional alloys that have at least one or two phases. It is thought that this difference in crystal structure and the number of phases is what causes it to exhibit higher hardness than conventional alloys.
[0109] Furthermore, the fact that the atomic concentration portions of each element shown in Figures 6(b), 6(c), 6(e), and 6(f) do not match indicates that there are at least three phases in the crystal structure with different elemental concentrations. [Industrial applicability]
[0110] The high-entropy alloy obtained by the present invention is suitable for various applications such as structural materials like blankets in nuclear fusion reactors, cemented carbide materials, and functional materials. [Explanation of Symbols]
[0111] S10...dissolution process S11…First early melting process S12…Second early melting process S13…Third early melting process S14…Late dissolution process S20…Cooling process S30…Homogenization process
Claims
1. It is a high-entropy alloy, It contains each of the elements W (tungsten), Si (silicon), Fe (iron), Cr (chromium), and V (vanadium) in amounts of 5 at% to 35 at%, with the remainder being unavoidable impurities. The content of the aforementioned unavoidable impurities is 1% by mass or less. A multiphase high-entropy alloy having a Vickers hardness of 1100 to 1800 (HV) and possessing a crystalline structure with at least three phases having different elemental concentrations.
2. Mixing entropy ΔS mix However, the high-entropy alloy according to claim 1, wherein the entropy is 1.5R or greater.
3. A method for producing a high-entropy alloy according to claim 1, A dissolution step in which raw materials containing each of the aforementioned elements are dissolved, A cooling step for cooling the molten metal in the melting step, A method for producing a high-entropy alloy, comprising a homogenization step of heating and pressurizing the high-entropy alloy cooled in the cooling step to homogenize it.
4. The method for producing a high-entropy alloy according to claim 3, wherein the homogenization step is a step of heating and pressurizing by hot isostatic working or hot pressing.
5. The aforementioned dissolution step is, A first pre-dissolution step for dissolving Si (silicon) and W (tungsten), a second pre-dissolution step for dissolving Cr (chromium) and W (tungsten), and a third pre-dissolution step for dissolving Fe (iron) and W (tungsten), A method for producing a high-entropy alloy according to claim 3 or claim 4, comprising a later dissolution step of mixing and dissolving the products obtained in the first, second, and third pre-dissolution steps, respectively, and V (vanadium).
Citation Information
Patent Citations
High entropy alloy for exterior component
JP2019163535A
Multi-component alloy excelling in balance of softening resistance, strength and elongation, and wear resistance
JP2021101035A
Powder made of multicomponent alloy and compact
JP2022143156A
Powder and compact made of multi-component alloy
JP2022180747A
Multi-component alloy
JP6979184B2